(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2025)
Folktale is an indispensable component of folklore, serving as a vital medium for moral instruction and value transmission within traditional societies. This study investigates the didactic and cross-cultural functions of folktales, using The Ant and the Grasshopper as a case study to illustrate how narrative art reinforces communal ethics such as hard work, foresight, and social responsibility. Folklore, as an umbrella term, encompasses three broad categories—verbal lore, material lore, and customary lore. Within this framework, folktale belongs to verbal lore, which embodies the spoken art forms through which a society expresses its worldview, moral philosophy, and collective identity. The study adopts a comparative and interpretive approach, examining parallels between the moral lessons of The Ant and the Grasshopper and similar tales from Igbo and Yoruba oral traditions. It argues that while folktales are locally grounded in the experiences and beliefs of a people, they often reveal universal human concerns and ethical ideals that transcend cultural boundaries. By analysing the symbolic use of animal characters and the narrative strategies employed by traditional storytellers, the study underscores the enduring relevance of folktales as tools for moral education and cultural continuity in African societies.